Adherence to Current COPD Guidelines in Turkey. (22nd January 2016) - Turan, Onur; Emre, Julide Celdir; Deniz, Sami; Baysak, Aysegul; Turan, Pakize Ayse; Mirici, Arzu
ABSTRACT: I ntroduction-objective : Despite the availability of national and international guidelines, chronic obstructive pulmonary diseases (COPD) treatment is not always prescribed according to these recommendations. We aimed to see if COPD patients in Turkey have been treated appropriately according to COPD guidelines. M ethods : This is a cross-sectional study carried out in six different chest diseases clinics. The COPD outpatients were categorized by spirometry classification (SC) and the combined classification (CC) of COPD. The treatment protocols were evaluated to check whether they were suitable for both classifications. R esults : Overall, 307 patients were included in the study. Of the treatment protocols, 40.4% were suitable for both classifications: 30.9% for CC and 20.8% for SC. A total of 51.8% of the patients were reported to be using an unsuitable therapy for SC and 38.4% for CC. Ninety-eight per cent of the unsuitable treatment was overtreatment. Fifty-eight per cent of the patients were using LABA + LAMA + ICS. Improper ICS usage was identified in 97.1% in CC, 93.1% in SC. The cost savings of all patients in one year would be 17, 099 with an appropriate treatment protocol following COPD guidelines. C onclusion : The most common type of inappropriate COPD treatments is overtreatment, generally with ICS. As treatment protocols following COPD guidelines change over time, there is still a low rate of adherence by clinicians in their clinical practice to guideline recommendations. Awareness of these guidelines by pulmonary specialists should be improved.